Courtship, Mating Behavior, and Ovary Histology of the Nymph Parasitoid Psyllaephagus bliteus (Hymenoptera: Encyrtidae). Issue 2 (16th April 2021) - Favoreto, A L; Domingues, M M; Serrão, J E; Ribeiro, M F; Silva, C A D; Zanuncio, J C; Wilcken, C F
Abstract: The potential of the parasitoid Psyllaephagus bliteus Riek for the biological control of the eucalyptus pest Glycaspis brimblecombei Moore (Hemiptera: Aphalaridae) nymphs is high. This research sought to analyze the courtship, male competition, and mating behavior of P. bliteus at the proportions of 1:1 and 2:1 males to female in a Petri dish (5 cm diameter), and to describe the ovary histology of virgin and mated females of this parasitoid. At 1:1, males touch the antennae and thorax–abdomen of females during courtship, but females avoid mate attempts before they are 48 h old. At 2:1, the competition between male parasitoids inhibits mating. The histology of ovaries of virgin and mated P. bliteus females is similar, with two well-defined germarium and vitellarium regions, with oocytes at different developmental stages, including mature ones rich in yolk and with eggshell. A clearer understanding of the reproductive behavior and histology of P. bliteus aids in the use of this parasitoid for the biological control of G. brimblecombei .